THE IMPACT OF OBESITY ON THE DEVELOPMENT AND PROGRESSION OF SELECTED RESPIRATORY DISEASES — OBSTRUCTIVE SLEEP APNEA, ASTHMA, AND COVID-19 - Wojtanowska, Ewa; Jachimczak, Ewa; Jaruga, Paulina; Grodkowska-Szukała, Karolina; Kozicka, Julia; Paczyna, Julia; Mazur, Marcin; Gąsiorowska, Vanessa; Suszczyńska, Aleksandra; Wiatr, Angelika (International Journal of Innovative Technologies in Social Science, 2026)
Obesity (BMI ≥30 kg/m²) is a growing global health problem that significantly affects respiratory function and disease. Excess adipose tissue can alter lung mechanics, reducing respiratory system compliance and lowering functional residual capacity while increasing airway resistance, particularly when lying down. Concurrently, obesity promotes a chronic, low-grade inflammatory state through hypertrophic adipocytes and macrophage infiltration, resulting in the overproduction of cytokines (e.g. IL-6 and TNF-α), adipokines (e.g. leptin) and mediators (e.g. HMGB1). These mechanical and inflammatory changes contribute to airway remodelling, endothelial dysfunction and an increased susceptibility to chronic and infectious respiratory diseases. This review summarises the current evidence on the impact of obesity on asthma, obstructive sleep apnoea (OSA), and SARS-CoV-2 infection. In asthma, obesity defines a distinct phenotype that is often difficult to treat, characterised by more persistent disease, a reduced response to inhaled glucocorticoids and spirometric changes that improve with weight loss. In OSA, obesity — particularly central and visceral fat — narrows the upper airway, destabilises ventilatory control, and markedly increases disease prevalence and severity. Indices of abdominal adiposity correlate more strongly with apnoea–hypopnoea burden than BMI alone. In the context of SARS-CoV-2 infection, obesity is a major risk factor for severe disease, higher rates of hospitalisation, ICU admission, ARDS and death, with risk rising across obesity classes. Obese patients also more often require invasive ventilation or ECMO, and they may experience prolonged respiratory impairment and long-term symptoms of post-viral fatigue.